2009
DOI: 10.1037/a0015535
|View full text |Cite
|
Sign up to set email alerts
|

Separable brain systems supporting cued versus self-initiated realization of delayed intentions.

Abstract: In everyday life, one can link anticipated specific cues (e.g. visiting a restaurant) with desired actions (e.g., ordering a healthy meal). Alternatively, intentions such as "I intend to eat more healthily" present the option to act when one encounters the same cue. In the first case, a specific cue triggers a specific action; in the second, one must act in a more self-initiated manner. The authors compared such scenarios using functional magnetic resonance imaging. Participants were either instructed to respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
122
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 65 publications
21
122
2
Order By: Relevance
“…In version 2 of the task, response confusions (i.e., pressing the wrong PM response button on a PM retrieval trial) were rare (4% of PM retrieval trials). PM accuracy in the present study was therefore comparable with previous studies of PM Gilbert et al, 2009) despite a mean delay between PM encoding and the opportunity to respond of just 10.8 s, much shorter than previous studies (typically on the order of several minutes or more). This suggests that the two-back task was sufficiently distracting to prevent continuous rehearsal of PM intentions (Einstein et al, 2003).…”
Section: Behavioral Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In version 2 of the task, response confusions (i.e., pressing the wrong PM response button on a PM retrieval trial) were rare (4% of PM retrieval trials). PM accuracy in the present study was therefore comparable with previous studies of PM Gilbert et al, 2009) despite a mean delay between PM encoding and the opportunity to respond of just 10.8 s, much shorter than previous studies (typically on the order of several minutes or more). This suggests that the two-back task was sufficiently distracting to prevent continuous rehearsal of PM intentions (Einstein et al, 2003).…”
Section: Behavioral Resultssupporting
confidence: 78%
“…On the one hand, univariate analyses indicated strong engagement of RLPFC while participants stored PM intentions, consistent with previous neuroimaging and neuropsychological studies indicating the involvement of this region in PM (Okuda et al, 1998;Burgess et al, 2000Burgess et al, , 2001Burgess et al, , 2003Simons et al, 2006;West, 2008;Gilbert et al, 2009;Reynolds et al, 2009;Uretzky and Gilboa, 2010). However, it was not possible to decode the content of those intentions from patterns of activity within RLPFC (unlike widespread posterior brain regions).…”
Section: Functional Connectivity Analysissupporting
confidence: 69%
See 1 more Smart Citation
“…Third, there is the interface between emotion and cognition, which is often the role of the prefrontal region. Small changes in the phrasing of the task instructions emphasizing either the action that needed to be carried out, or the reward that would be won, led to differential patterns of activation within rostral prefrontal cortex (Gilbert, Gollwitzer, Cohen, Oettingen, & Burgess, 2009; Figure 3). Fourth, differences in instructions are likely to call upon different processes to complete a task, seemingly independent of emotional/ cognition interplay (Floden, Vallesi, & Stuss, 2011;Stuss et al, 2000).…”
Section: Reasons For Weak Psychometric Qualities In Executive Tasksmentioning
confidence: 99%
“…For instance, Bayer, Achtziger, Gollwitzer, and Moskowitz ( 2009 ) found that implementation intentions encouraged successful pursuit of a goal even when the critical cue was presented subliminally, that is, when it was not consciously recognized. Moreover, studies of the human brain have found evidence that implementation intentions change action control from slow top-down to fast bottom-up processes (e.g., Gilbert, Gollwitzer, Cohen, Oettingen, & Burgess, 2009 ;Schweiger Gallo, Keil, McCulloch, Rockstroh, & Gollwitzer, 2009 ;Hallam et al, 2015 ). In summary, implementation intentions strategically automate the control of goal-directed actions, instantly and effi ciently activating the action response linked to a critical situation when the individual enters it.…”
Section: Controlling Actions By Goals and Implementation Intentionsmentioning
confidence: 99%